2023
DOI: 10.1038/s41598-023-36928-1
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative and near-comprehensive North Pacific humpback whale photo-ID dataset

Abstract: We present an ocean-basin-scale dataset that includes tail fluke photographic identification (photo-ID) and encounter data for most living individual humpback whales (Megaptera novaeangliae) in the North Pacific Ocean. The dataset was built through a broad collaboration combining 39 separate curated photo-ID catalogs, supplemented with community science data. Data from throughout the North Pacific were aggregated into 13 regions, including six breeding regions, six feeding regions, and one migratory corridor. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…For this study, all available North Pacific humpback whale photo-ID data from a research collaboration of 46 organizations and 4292 community science contributors were aggregated within a study period of 2001 through 2022, and reconciled in a single dataset through the research collaboration and community science Web platform Happywhale.com. This dataset is fully described by Cheeseman et al [18]. Photo-ID data for the purpose of this study consisted of encounters of individually identified whales, with associated dates and geographical locations.…”
Section: Sample Collection and Matching Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, all available North Pacific humpback whale photo-ID data from a research collaboration of 46 organizations and 4292 community science contributors were aggregated within a study period of 2001 through 2022, and reconciled in a single dataset through the research collaboration and community science Web platform Happywhale.com. This dataset is fully described by Cheeseman et al [18]. Photo-ID data for the purpose of this study consisted of encounters of individually identified whales, with associated dates and geographical locations.…”
Section: Sample Collection and Matching Methodsmentioning
confidence: 99%
“…Furthermore, the infrequent generation of updated population estimates may fail to capture rapid changes in whale populations due to anthropogenic disturbances or environmental fluctuations [ 17 ]. To address these challenges, we have drawn on an innovative ocean-basin-wide collaboration [ 18 ] to cost-effectively generate a time series of relatively precise abundance estimates for a long-distance migrating species, the humpback whale ( Megaptera novaeangliae ) in the North Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the North Pacific, humpback whales migrate annually between highlatitude summer feeding grounds along the Northern Pacific rim from Russia, through the Aleutian Islands, the Bering Sea, Alaska, Northern British Columbia, to the Northern US West Coast, and low latitude winter breeding areas including Japan, the Philippines, Hawai'i, Mexico and Central America [47][48][49][50][51]. The Hawaiian archipelago is considered the principal breeding area for the North Pacific metapopulation, with more than 10 000 whales visiting the island chain every year [47,52]. The arrival and departure of humpback whales in Hawai'i is staggered and segregated by age-class, sex and reproductive condition [53], with peak abundance in the islands typically occurring in February and March [54,55].…”
Section: Introductionmentioning
confidence: 99%